The code. Season 1 [videorecording (DVD)]. - Spielman, Dan; Zukerman, Ashley; Perovic, Adele (Acorn, 2015)
Several interweaving storylines that start with a mysterious accident and the death of an Aboriginal girl in the outback. Her former teacher, Alex, becomes involved with journalist Ned Banks and his brother, Jesse, a genius computer hacker, to try to unravel the mystery. When the brothers uncover video footage of the crime, they are targeted by powerful and dangerous figures that may be connected to the highest levels of national politics.